Beyond the looking glass The AI Mirror: How to Reclaim Our Humanity in an Age of Machine Thinking Shannon Vallor Oxford University Press, 2024. 272 pp - Spezio, Michael (Science (American Association for the Advancement of Science), 2024)
An ethicist advocates a moral framework for technology.